Analisis Kelayakan Sistem Monitoring dan Kontrol Lampu Menggunakan Web Server Berbasis Raspberry Pi - Maslan - Maslan; Hendri Hendri (Jurusan Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2017)
As technology develops progressively over time, system developers continue to strive to create more efficient monitoring systems. The problem that often happens is the control room and light control is currently not utilize an integrated system based web server. Room control systems still utilize large equipment such as televisions and large computers, so that every problem occurs in the room is difficult to control. From these problems then the purpose of this study to create an efficient control system that utilizes super mini-based Raspberry Pi. To create a system based on Raspberry P microcontroller then required an initial observation to perform the feasibility test on the system to be developed. The feasibility test system is the successful monitoring of the room using CCTV (Closed Circuit Television) equipment and control the lamp automatically by using prototyping method. The CCTV feasibility test is viewed from the resolution while the control of room light control is seen from the success of controlling the life of the lights on the test. Based on the testing concluded that the monitoring of the room using Raspberry Pi-based web server is feasible to use, seen the test results when the light control goes smoothly, because the lights controlled through the webserver managed to live and die. Similarly, when monitoring the room with live CCTV also runs well. And while conducting Room monitoring experiments with Webcam at 800 x 600 resolution there is a lot of variation value of frame rate sometimes up and down. The up and down frame is caused by an unstable network connection.